2018
DOI: 10.22158/jbtp.v6n2p154
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Organizational Performance by Knowledge Sharing

Abstract: <em>Knowledge management can be regarded as one of the key processes of organizational learning. It is well accepted that learning organizations can enhance their capability and hence competitiveness and performance through learning. Recognizing the importance of knowledge management, researchers are interested in exploring knowledge sharing activities because such activities are the cornerstone of other knowledge management activities. It is argued that a fundamental purpose of managing knowledge is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
1
6
0
Order By: Relevance
“…According to Sigalaa and Chalkiti (2015) and Asiedu, Abah, and Dei (2022), different KS strategies are used to share different types of knowledge. As indicated by Chau (2018), it is not difficult to share explicit knowledge as it is already codified and stored in the organisation repository as databases, documents or manuals ready to be used by employees. However, other studies (Appel-Meulenbroek et al, 2018;Chau, 2018;Al Kashari and Al Taheri, 2019;Asiedu et al 2022;Zeng et al, 2022) show that it is a challenge for employees to share tacit knowledge because of its subjective nature as it comprises of individuals' traits such as attitude, thought and emotions, which are derived from human perceptions.…”
Section: Knowledge Sharing In the Organisationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Sigalaa and Chalkiti (2015) and Asiedu, Abah, and Dei (2022), different KS strategies are used to share different types of knowledge. As indicated by Chau (2018), it is not difficult to share explicit knowledge as it is already codified and stored in the organisation repository as databases, documents or manuals ready to be used by employees. However, other studies (Appel-Meulenbroek et al, 2018;Chau, 2018;Al Kashari and Al Taheri, 2019;Asiedu et al 2022;Zeng et al, 2022) show that it is a challenge for employees to share tacit knowledge because of its subjective nature as it comprises of individuals' traits such as attitude, thought and emotions, which are derived from human perceptions.…”
Section: Knowledge Sharing In the Organisationmentioning
confidence: 99%
“…As indicated by Chau (2018), it is not difficult to share explicit knowledge as it is already codified and stored in the organisation repository as databases, documents or manuals ready to be used by employees. However, other studies (Appel-Meulenbroek et al, 2018;Chau, 2018;Al Kashari and Al Taheri, 2019;Asiedu et al 2022;Zeng et al, 2022) show that it is a challenge for employees to share tacit knowledge because of its subjective nature as it comprises of individuals' traits such as attitude, thought and emotions, which are derived from human perceptions. Thus, negative perceptions are likely to affect employees' knowledge sharing behaviours and endanger KS in the organisation (Vines, Jones and McCarthy 2015;Girard and Girard, 2015).…”
Section: Knowledge Sharing In the Organisationmentioning
confidence: 99%
See 1 more Smart Citation
“…(Razmerita, Kirchner & Nielsen, 2016) who found that employees like helping others was a factor that had relationship with knowledge sharing of the employees which is consistent with the findings of researchers (Islam, Jantan, Khan, Rahman & Monshi, 2018;Irma Susanty & Charles Wood, 2011) Self-Efficacy: For the employees to voluntarily share knowledge they must have the sense of selfefficacy that their experience and knowledge is valuable for the organization (Staplehurst & Ragsdell, 2010). In the model proposed by (Chau, 2018) self-efficacy and employee attitude were important factors for knowledge sharing. Employees share knowledge if they feel that their knowledge is useful for the organization (Razmerita, Kirchner & Nielsen, 2016) and it was found to have a strong relationship with knowledge sharing by (Akram, Naeem Shahid, Iqbal & Rabia Akram, 2019).…”
Section: Knowledge Sharing Factors In Sme's and Large Organizationsmentioning
confidence: 99%
“…The role of knowledge sharing in organizations will contribute to employee performance (Olan et al, 2015). Another researcher defines knowledge sharing as a process in which individuals exchange their knowledge, both tacit knowledge and explicit knowledge (Chau, 2018). Several studies stated that knowledge sharing has a significant positive effect on performance.…”
mentioning
confidence: 99%